Diskursus Khilafah dalam Kajian Fiqh Siyasah Klasik dan Kontemporer - Marzuki, Ismail (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
Until now, the Muslim community in Indonesia is flooded with massive information about the discourse of the obligation to establish a caliphate. Some argue that establishing a caliphate is an obligation for all Muslims. This article discusses the caliphate discourse in the study of fiqh al-siyasa in the classical era and the contemporary era. The discourse on the caliphate in the contemporary era has warmed up after the collapse of the Ottoman Turks in 1924, the debate on theme of the caliphate in the contemporary era is about whether there is a standard form of government and Islam, the legal status of establishing a caliphate, and so on. This theme is different from the themes of the discussion of the caliphate in the classical era, in this era, themes the caliphate revolved around aspects of Islamic leadership values, such as procedures for choosing a caliph/leader, political ethics that must be held by leaders and other state officials.